THE LAW OF TERROR ACCORDING TO THE QUR'AN SURAH AL-ANFAL, VERSE 60 (Responding to the Phenomenon of Terror in Indonesia) - Zuhri, Ahmad (AL-MANHAJ: Jurnal Hukum dan Pranata Sosial Islam, 2021)
Understanding related to the values of jihad can be misunderstood, so that it can lead to the wrong context, which leads to an act of terrorism. The real impact can be witnessed through acts of terrorism that have occurred in Indonesia. The actions that took place had a negative impact on people's lives in Indonesia, which created a feeling of fear, anxiety, and worry. This research is included in the qualitative research category with the aim of analyzing the terror law based on Al-Anfal verse 60, which is associated with the terror phenomenon that occurred in Indonesia. The research method approach uses a literature study approach that comes from interpretations and related references. The results of the research show that the phenomenon of terror that occurs is caused by a misunderstanding in the context of the form of jihad and the values of martyrdom, which are often used as an excuse for carrying out acts of terror. So that terror and acts of terrorism are contrary to Islamic teachings. Although the terms "terror" and "terrorism" may not be explicitly mentioned, the values and principles contained in the Quran provide a basis for the conclusion that terror and terrorism are forbidden in Islam.